Education in Sub-Saharan Africa : Comparing Faith-Inspired, Private Secular, and Public Schools - Wodon, Quentin (Washington, DC: World Bank, 2013)
The purpose of this study is to build a stronger evidence base on the role of faith-inspired, private secular, and public schools in sub-Saharan Africa using nationally representative household surveys as well as qualitative data. Six main findings emerge from the study: (1) Across a sample of 16 countries, the average market share for faith-inspired schools is at 10-15 percent, and the market share for private secular schools is of a similar order of magnitude; (2) On average faith-inspired schools do not reach the poor more than other groups; they also do not reach the poor more than public schools, but they do reach the poor significantly more than private secular schools; (3) The cost of faith-inspired schools for households is higher than that of public schools, possibly because of a lack of access to public funding, but lower than that of private secular schools; (4) Faith-inspired and private secular schools have higher satisfaction rates among parents than public schools; (5) Parents using faith-inspired schools place a stronger emphasis on religious education and moral values; and (6) Students in faith-inspired and private schools perform better than those in public schools, but this may be due in part to self-selection.